2023
DOI: 10.3390/ijerph20043702
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genetic Characterization of MERS-Related Coronavirus Isolated from Nathusius’ Pipistrelle (Pipistrellus nathusii) near Zvenigorod (Moscow Region, Russia)

Abstract: Being diverse and widely distributed globally, bats are a known reservoir of a series of emerging zoonotic viruses. We studied fecal viromes of twenty-six bats captured in 2015 in the Moscow Region and found 13 of 26 (50%) samples to be coronavirus positive. Of P. nathusii (the Nathusius’ pipistrelle), 3 of 6 samples were carriers of a novel MERS-related betacoronavirus. We sequenced and assembled the complete genome of this betacoronavirus and named it MOW-BatCoV strain 15-22. Whole genome phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…The cellular receptors used by PN-βCoV are currently unknown. However, in silico and phylogenetic analysis suggests that this virus might have affinity for bat DPP4 ( 49 ). DPP4 expression has been demonstrated in epithelial cells of the intestinal tract, but not in the respiratory tract, in a species closely related to Nathusius’s Pipistrelle Bats ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular receptors used by PN-βCoV are currently unknown. However, in silico and phylogenetic analysis suggests that this virus might have affinity for bat DPP4 ( 49 ). DPP4 expression has been demonstrated in epithelial cells of the intestinal tract, but not in the respiratory tract, in a species closely related to Nathusius’s Pipistrelle Bats ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two novel bat merbecoviruses with complete genome sequenced, MOW-15-22 and PN-βCoV (designated PnNL2018B in this study), were independently reported by research teams in Russia and Netherlands 35,36 (Fig. 1a).…”
Section: Phylogenetic and Structural Analyses Suggest Ace2 Usage By M...mentioning
confidence: 84%
“…In our quest to identify receptors for representative merbecoviruses, we noticed these two viruses form a distinct clade and exhibited an unknown receptor usage. At the complete-genome level, MOW-15-22 and PnNL2018B share less genetic similarity with the African bat coronaviruses NeoCoV and PDF-2180 but show greater genetic homology with a Italian bat merbecovirus (Hsavll/ltaly/206645-40/2011) and a DPP4-using virus HKU25 35,40 ( Fig. 1c ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations